Complex systems and applied linguistics - Larsen-Freeman, Diane; Cameron, Lynne (Oxford applied linguistics, 2008)
"Complex Systems and Applied Linguistics introduces key concepts in complexity theory to readers concerned with language, its learning, and its use. The book demonstrates the applicability and usefulness of these concepts to a range of areas in applied linguistics including first and second language development, language teaching, and discourse analysis. It concludes with a chapter that discusses suitable approaches to research investigations. This book will be invaluable for readers who want to understand recent developments in the field that draw on complexity theory, including dynamic systems theory, ecological approaches, and emergentism."